HIV/AIDS-related stigma and HIV test uptake in Ghana: Evidence from the 2008 demographic and health survey - Novignon, J.; Novignon, N.; Aryeetey, G.; Nonvignon, J. (Etude de la Population Africaine, 2014)
The study examined the association between HIV test uptake and socioeconomic characteristics of individuals, including HIV-related stigma behaviours. The study also investigated the socioeconomic determinants of HIV-related stigma in Ghana. Cross tabulations and logistic regression techniques were applied to data from the 2008 Ghana Demographic and Health Survey. The results showed significantly low HIV test uptake and some level of HIV-related stigma prevalence in Ghana. Higher wealth status, educational attainment and HIV-related stigma were significant determinants of HIV test uptake. Aside wealth status and education, rural place of residence and religious affiliation were positive and significant determinants of HIV-related stigma. The findings call for comprehensive HIV education including treatment, prevention and care. Legislations to discourage stigma and improve HIV-testing will be critical policy steps in the right direction. © 2014, Union for African Population Studies. All rights reserved.
Keywords: Ghana; HIV test uptake; HIV/AIDS; Logistic regression; Stigma